Axillary staging with 18F-FDG PET/CT in early breast cancer: impact of tumor subtypes - Abdullah Gunes; Nuray Colapkulu-Akgul; Caner Akgul; Ibrahim Unlu; Saffet Cinar (Annals of Saudi Medicine, 2025)
BACKGROUND: Breast cancer is one of the most common cancers in women globally. Axillary lymph node metastasis remains one of the most independent prognostic factors in breast cancer. OBJECTIVE: Evaluate the diagnostic accuracy of 18F-FDG-PET/CT in detecting axillary lymph node metastasis based on immunohistochemical subtypes and its correlation with sentinel lymph node biopsy (SLNB) results. DESIGN: A retrospective cohort SETTING: Tertiary oncology center in Turkiye PATIENTS AND METHODS: Patients diagnosed with early-stage invasive ductal breast cancer and who underwent preoperative F-18 fluorodeoxyglucose positron emission computed tomography (18F-FDG PET/CT) evaluation were included in the study. Patients were divided into five immunohistochemical subtypes: Luminal A, Luminal B HER2 (−) (human epidermal growth factor receptor 2), Luminal B HER2 (+), HER2 (+), and triple negative. SLNB and SUVmax (Maximum Standard Unit Value) results were compared. MAIN OUTCOME MEASURES: Diagnostic accuracy of 18F-FDG PET/CT for detecting axillary metastasis was the primary outcome. Interrater reliability testing in determining the agreement between 18F-FDG PET/CT and SLNB was the secondary outcome. SAMPLE SIZE: 248 RESULTS: The sensitivity, specificity, PPV, NPV and accuracy of 18F-FDG-PET/CT for detecting axillary metastasis were 62%, 92%, 88%, 71% and 77%, respectively. Cohen's Kappa coefficient (0.54) showed moderate agreement with SLNB (P<.001). Tumors with positive HER2 gene amplification [HER2 (+) and Luminal B HER2 (+) have higher sensitivity than other subtypes (Luminal A, Luminal B HER2 (−) and triple negative). HER2 gene amplification also increases the agreement between 18F-FDG-PET/CT and SLNB results. CONCLUSION: 18F-FDG-PET/CT has a high specificity but low sensitivity for ipsilateral axillary metastasis in invasive ductal carcinoma. The presence of HER2 gene amplification can increase sensitivity and concordance with SLNB. LIMITATIONS: Retrospective design and limited number of patients for each subtype.